Evaluation of the corrosive potential of soils in pipelines used for water transportation in the Sertão of Pernambuco - Silva, Érika Larissa Rodrigues da; Melo, Adriana Nery Souto Paz de; Silva, Suzana Pedroza da (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
In the midst of the country's water emergency, mainly in the northeastern backwoods, the water mains are consecrated as an effective means of transportation of water. The soil is widely exploited in the constructions one of the most influential corrosive means of the mains. Corrosion can cause cracks and ruptures of built structures causing economic and environmental damage. Aiming to prevent such incidents, the objective was the soil corrosivity was evaluated and the loss of mass in ductile cast iron pipes was monitored under the action of the soil. In the soil chemical analyzes, pH, Ca, Mg, P, K, Na, Al, H, Fe, Cu, Zn, Mn and organic matter (OM), organic carbon (OC) were calculated and the sum of bases (CTC), percentage of saturation by aluminum (m%) and percentage of saturation by bases (V%). For soil corrosivity the Steinrath index was used, being analyzed pH, moisture content, resistivity, chloride and sulfate ions. The ductile iron tube mass loss tests were performed using soil samples as a corrosive medium, monitoring temperature, resistivity, and loss of mass by corrosion. The results showed that the soils are not very corrosive and the duct presents good resistance to corrosion, although they present loss of mass throughout the period of the use. It is possible to conclude that the soil in contact with the water transport ducts presents low aggressiveness.